The effectiveness of nutrition education for care takers at Al-Sabah children hospital in patient therapeutic feeding center, Juba South Sudan. - Alumai, John Bosco (Open Science Journal, 2020)
Abstract Background A key part of treating and preventing malnutrition is the provision of effective nutrition education to the clients and caretakers so that they can self-manage their nutrition needs even after discharge from the hospital. For effective nutrition education, three factors are paramount; The successful transfer of knowledge and skills, client motivation to act on the acquired skills and knowledge and ensuring that the patient is able to understand and put to practice the educational messages given. Methods The study used cross sectional design with mixed method of data collection that involved 83 caretakers of admitted SAM children at Al-Sabah children hospital ITC, Sample size was determined using Cochran 1975, interviewer administered questionnaires and focus group discussion guide were the tools used in collecting data. Data set was generated using EPI info and analyzed using SPSS version 21, the analyzed descriptive data was triangulated with the qualitative data collected using FGD. Results The majority of the caretakers were female 78 (94%) of which 68 (81.9%) were mothers to the children that were admitted. Only 8 (9.6%) of the respondents were found to have attained effective nutrition education and majority of the respondents were found not to be recalling the information they were given during the education session. Conclusion As per the guidelines adapted by the ministry of health republic of South Sudan, the nutrition education sessions conducted was found not be effective as most of the clients could not even recall the information given.